The Mediating Role of Corporate Social Responsibility in the Relationship Between Ownership Structure, Firm Characteristics, and Tax Avoidance - Audeelya Putri Ellena; Agustin Palupi (Journal of Creative Power and Ambition (JCPA), 2026)
This study analyzes the effect of institutional ownership, managerial ownership, firm size, profitability, and board gender diversity on tax avoidance through corporate social responsibility (CSR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Using purposive sampling, 110 companies (330 observations) were analyzed with multiple regression based on data from the IDX, annual reports, and sustainability reports. The results indicate that profitability (ROA) has a negative and significant effect on the Effective Tax Rate (ETR), suggesting higher tax compliance among more profitable firms, while institutional ownership, managerial ownership, firm size, and board gender diversity show no significant effect on tax avoidance, and CSR does not mediate the relationship between these variables and tax avoidance.